The ultimate guide to weight training for hockey - Price, Robert G., ....- (2005)
The Ultimate Guide to Weight Training for Hockey is the most comprehensive and up-to-date hockey-specific training guide in the world today. It contains descriptions and photographs of nearly 100 of the most effective weight training, flexibility, and abdominal exercises used by athletes worldwide. This book features year-round hockey-specific weight-training programs guaranteed to improve your performance and get you results. No other hockey book to date has been so well designed, so easy to use, and so committed to weight training. This book will have players increasing speed, strength, power, agility, and stamina while reducing chances of injury. This book guarantees more velocity and accuracy on slap shots, more power on checks, and more endurance making it possible to give it your all until the final whistle. Both beginners and advanced athletes and weight trainers can follow this book and utilize its programs. From recreational to professional, thousands of athletes all over the world are already benefiting from this book and its techniques, and now you can too!
Maximize your athletic potential on ice! - pre-season, in-season and off-season sport-specific programs designed to: increase speed, eliminate fatigue,prevent injuries and improve velocity on your slap shot!
Keywords: Hockey ; krachttraining